PENGADAAN PETI KEMAS DALAM MENUNJANG EKSPOR IMPOR NON –MIGAS DI PELABUHAN TANJUNG PERAK SURABAYA PERIODE 2011 –2015 - JEFLIEN JEFLIEN (CALYPTRA, 2018)
This study aimed to examine the internal factor and external factor that can support or inhibit the development PT. Surabaya Container Terminal to support the role of containers in import export activities through Tanjung Perak Port. This study used a qualitative approach of data used in the form of secondary data and primary data. Primary data in this study was conducted through interviews, secondary data in the form of documents \provided by PT. Surabaya Container Terminal (TPS) such as documentation.The findings from this study indicate that PT. Surabaya Container Terminal has many potentials that can support the role of container in supporting import export, PT. Surabaya Container Terminal can provide container yard, loading and unloading tools that can support import export activities, PT. Surabaya Container Terminal has many service is container loading service, container unloading service, container receiving service and container dispending services. Obstacles encountered in this study are divided into 2 (two) problems of external problems and internal problems. External problems including bad weather can affect the timing of vessels as well as for the spread of container terms in import or export societies in Indonesia, which often creates problems in terms of responsibility for delivery of goods. Internal problems in this study include the complete lack of loading and unloading equipment and not all the equipment in PT. Surabaya Container Terminal uses modern technology, lack of skill from officer handling equipment for loading and unloading of container freight causing reduced loading and unloading speed, and less extent of container container field at PT. Surabaya Container Terminal which can lead to accumulation of containers that cross the line.